Prevalence and Intensity of Gastrointestinal Parasites in Donkeys in Selected Abattoirs in Kenya - Nancy Mulwa; Samuel Githigia; Davis Karanja; Cecilia Mbae; Eberhard Zeyhle; Erastus Mulinge; Japhet Magambo; Kennedy Ogolla (Scientifica)
The aim of this study was to determine the prevalence and intensity of gastrointestinal parasites in donkeys slaughtered in Kinamba, Mogotio, and Lodwar slaughterhouses and their association with several host factors. A survey was done between July and September 2017 in three slaughterhouses. Faecal samples were collected per rectum from all the study donkeys for faecal egg counts (EPG) and morphological identification of the eggs. At slaughter, the gastrointestinal tracts were opened and examined visually, and all helminth parasites collected were subjected to morphological identification. Prevalence and intensity were calculated based on the helminth identified and EPG. A total of 282 donkeys were sampled. A majority of the donkeys (89%) were in poor body condition. Ten helminth parasite species were identified in 85.5% donkeys. They were Strongylus vulgaris (52.8%), Parascaris equorum (20.2%), Strongylus edentatus (12.1%), Anaplocephala perfoliata (10.3%), Setaria equina (3.5%) Anaplocephala magna (2.5%), Cylicocyclus auriculatus (2.1%), Cyathostomum species (1.8%), Strongylus equinus (0.4%), and Triodontophorus serratus (0.4%). A significant percentage (55.3%) had no eggs in their feces, 39% had low infection, 5% had medium, and only 0.7% were heavily infected. Prevalence rates via use of the EPG showed Strongyles (44.7%), Parascaris equorum (5.3%), Oxyuris equi (11%), Triodontophorus tenuicolis (0.7%), Habronema species (0.7%), and cestodes eggs (0.4%). No significant differences were observed between fecal Strongylus egg count and age, sex, and pregnancy status. However, donkeys with poor body condition shed more Strongylus eggs in feces. Helminth infections are prevalent in donkeys in Kenya; however, this is not reflected in coprological analyses. These helminth parasites may contribute to poor body condition, ill health, and poor productivity of donkeys.